Sharia Financial Literacy and Good Corporate Governance for Generation Z: Study in Sharia Banks in Indonesia - Lutfillah, Novrida Qudsi Lutfillah; Yeni Agustin Novitasari; Atik Andhayani (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
The challenge faced by Sharia banks in attracting Generation Z as their primary customers lies in the limited awareness of the impact of Sharia financial literacy and Good Corporate Governance (GCG) practices on saving decisions. This gap hinders the ability of Sharia banks to effectively position themselves as trusted institutions for this demographic. This study aims to investigate the relationship between Sharia financial literacy and GCG practices on saving decisions among Generation Z in Malang City. Using multiple linear regression analysis, the research reveals that increased Sharia financial literacy and effective GCG practices positively influence saving decisions by fostering trust and customer satisfaction with Sharia banks’ adherence to Sharia principles. These findings emphasize the need for Sharia banks and regulators to actively promote financial literacy and enforce strong GCG practices to enhance their competitiveness among Generation Z. Tantangan yang dihadapi bank syariah dalam menarik Generasi Z sebagai nasabah utamanya terletak pada terbatasnya kesadaran akan dampak literasi keuangan syariah dan praktik Good Corporate Governance (GCG) terhadap keputusan menabung. Kesenjangan ini menghambat kemampuan bank syariah untuk secara efektif memposisikan diri sebagai lembaga terpercaya bagi Generasi Z. Penelitian ini bertujuan untuk mengetahui hubungan literasi keuangan syariah dan praktik GCG terhadap keputusan menabung pada Generasi Z di Kota Malang. Dengan menggunakan analisis regresi linier berganda, penelitian ini mengungkapkan bahwa peningkatan literasi keuangan syariah dan praktik GCG yang efektif berpengaruh positif terhadap keputusan menabung dengan menumbuhkan kepercayaan dan kepuasan nasabah terhadap kepatuhan bank syariah terhadap prinsip-prinsip syariah. Temuan ini menekankan perlunya bank syariah dan regulator untuk secara aktif mempromosikan literasi keuangan dan menegakkan praktik GCG yang kuat untuk meningkatkan daya saing bank syariah di kalangan Generasi Z.